The last post-cold war socialist federation ethnicity, ideology and democracy in Ethiopia - Abebe, Semahagn Gashu (Federalism studies, 2016)
This book assesses the Ethiopian ethnic federal system from the perspective of the principles of socialist federations and other Marxist oriented policies pursued by the ruling Ethiopian Revolutionary Democratic Front (EPRDF). Read less